2004
DOI: 10.1111/j.1365-313x.2004.02192.x
|View full text |Cite
|
Sign up to set email alerts
|

ABF2, an ABRE‐binding bZIP factor, is an essential component of glucose signaling and its overexpression affects multiple stress tolerance

Abstract: SummaryPhytohormone abscisic acid (ABA) regulates stress-responsive gene expression during vegetative growth, which is mediated largely by cis-elements sharing the ACGTGGC consensus. Although many transcription factors are known to bind the elements in vitro, only a few have been demonstrated to have in vivo functions and their specific roles in ABA/stress responses are mostly unknown. Here, we report that ABF2, an ABF subfamily member of bZIP proteins interacting with the ABA-responsive elements, is involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
335
2
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(359 citation statements)
references
References 52 publications
18
335
2
4
Order By: Relevance
“…2B, C). Kim et al reported that ABF2 over-expressed plants were insensitive to ABA for leaves and hyper-sensitive to ABA for roots (12). OsAREB1 in our study is the most homologous gene to ABF2, OsAREB1 may have similar response.…”
Section: Overexpression Of Osareb1 Alters Seedling Sensitivity To Abamentioning
confidence: 56%
See 1 more Smart Citation
“…2B, C). Kim et al reported that ABF2 over-expressed plants were insensitive to ABA for leaves and hyper-sensitive to ABA for roots (12). OsAREB1 in our study is the most homologous gene to ABF2, OsAREB1 may have similar response.…”
Section: Overexpression Of Osareb1 Alters Seedling Sensitivity To Abamentioning
confidence: 56%
“…These reported studies suggest that ABFs may function in different stress response pathways; i.e. ABF1 in cold signaling; ABF2 in salt, drought, heat and glucose signaling pathways (12,13); ABF3 in salt signaling; ABF4 in cold, salt, and drought signaling pathways (12).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that activation of a specific transcription factor can often result in expression of many functional genes related to stresses. Many efforts have been reported to improve stress resistance of plants by over-expressing stress-responsive transcription factor genes such as DREB/ CBF (Liu et al 1998), ABF2 (Kim et al 2004), OSISAP1 (Mukhopadhyay et al 2004) and etc.…”
mentioning
confidence: 99%
“…ABI5 is a genetically identified ABA signaling component that plays an essential role in seed germination and ABA-triggered developmental arrest processes after germination in Arabidopsis. In contrast, ABFs or AREBs function mostly in the vegetative stage (Choi et al, 2000;Uno et al, 2000;Kang et al, 2002;Kim et al, 2004;Fujita et al, 2011). However, recent reports confirmed that the AREB/ ABF/ABI5 members are major targets of SnRK2 protein kinases in ABA core signaling Fujita et al, 2009).…”
mentioning
confidence: 99%
“…AREB1/ABF2 has been further documented for its posttranslational modification, which is related to its activity regulation (Fujita et al, 2005;Furihata et al, 2006). Thus far, SnRK2-AREB/ABF has been proven as a major module regulating ABA-mediated gene expression in response to abiotic stresses in Arabidopsis (Kim et al, 2004;Fujita et al, 2005;Furihata et al, 2006;Yoshida et al, 2010).…”
mentioning
confidence: 99%